2017
DOI: 10.1038/s41598-017-15499-y
|View full text |Cite
|
Sign up to set email alerts
|

Urban Seismology: on the origin of earth vibrations within a city

Abstract: Urban seismology has become an active research field in the recent years, both with seismological objectives, as obtaining better microzonation maps in highly populated areas, and with engineering objectives, as the monitoring of traffic or the surveying of historical buildings. We analyze here the seismic records obtained by a broad-band seismic station installed in the ICTJA-CSIC institute, located near the center of Barcelona city. Although this station was installed to introduce visitors to earth science d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 46 publications
10
76
1
1
Order By: Relevance
“…In the 1‐ to 20‐Hz frequency band, urban anthropogenic activities (Díaz et al, ) are likely to be the main source of the seismic noise recorded by the MeSO‐net stations, which are mainly located in schools. This is confirmed by the fact that daily and weekly variations are visible in the CC( t ) and d v / v ( t ) at most stations.…”
Section: Coseismic and Postseismic Response Of The Near Surface In Grmentioning
confidence: 99%
“…In the 1‐ to 20‐Hz frequency band, urban anthropogenic activities (Díaz et al, ) are likely to be the main source of the seismic noise recorded by the MeSO‐net stations, which are mainly located in schools. This is confirmed by the fact that daily and weekly variations are visible in the CC( t ) and d v / v ( t ) at most stations.…”
Section: Coseismic and Postseismic Response Of The Near Surface In Grmentioning
confidence: 99%
“…The idea is to involve the secondary school community in the recording and interpretation of seismic data acquired within cities. Previous results have shown that many citizen activities produce vibrations that can be recorded seismically, including traffic (Riahi and Gerstoft, 2015), subway systems (Sheen et al, 2009), music concerts (Green and Bowers, 2008) or football games (Díaz et al, 2017). The identification of the vibrations generated by this kind of sources is useful to correctly interpret ambient noise data, but also to attract the attention of mass media (journals, radio, TV) and social networks and be used as a valuable tool for spreading news related to seismology and, in general, Earth sciences to the main public.…”
Section: Introductionmentioning
confidence: 99%
“…The ambient seismic noise recorded by seismometers includes microseisms and anthropogenic or cultural noise. While microseisms are caused by the coupling between the ocean and the solid earth at frequencies mostly <1 Hz 1 , anthropogenic seismic noise, especially in urban areas, includes seismic signals generated by human activities such as moving people and industrial activities [2][3][4][5] . A recent study reported an increase in ambient seismic noise energy in response to an increase in the gross domestic product (GDP), which is associated with the magnitude of human activity 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since an increase in ambient noise energy can be attributed to a wide range of human activities, ambient seismic noise in urban areas tends to be stronger and more complex. For instance, Díaz et al 5 monitored road tra c and subway trains along an avenue about 150 m away for frequencies >1 Hz (maximum energy between 8-35 Hz) and 20-40 Hz band, respectively. They succeeded in detecting signals generated by various anthropogenic noise including rock concerts, football games, and road tra c. Considering the temporary absence of a speci c noise source, Green et al 7 monitored the ambient seismic noise during a complete shutdown of the subway system during an industrial strike, and found clearly evident reduction for frequencies >25 Hz within 100 m distance but no reduction at a distance of ~600 m from the nearest subway line.…”
Section: Introductionmentioning
confidence: 99%